2008
DOI: 10.1039/b800108a
|View full text |Cite
|
Sign up to set email alerts
|

The progression of strong and weak hydrogen bonds in a series of ethylenediammonium dithiocyanate derivatives—a new bonding protocol for macromolecules?

Abstract: The experimental charge densities for a series of sym-N-methyl-substituted ethylenediammonium dithiocyanate salts have been investigated based on low-temperature and high-resolution X-ray diffraction data. This series of organic dications provides both strong and weak hydrogen bonding networks that vary depending on the N-H : SCN(-) (donor/acceptor) ratios. The number of N-HN hydrogen bonds connected to each cation increases (linear to bifurcated) as the number of N-H donor groups increases. The bifurcated thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…At the interface of the CuS nanosheets, S atoms are exposed on the ridges and Cu atoms are embedded in the grooves (Figure b). The exposed S atoms have much weaker hydrogen bonding with H 2 O molecules, compared with that between O atoms and H 2 O molecules. As a result, the PAN@CuS fabric shows a lower water-evaporation enthalpy (Figure b). In addition, the sunflower-inspired hierarchical PAN@CuS fabric is further equipped in a heliotropic evaporation model.…”
mentioning
confidence: 99%
“…At the interface of the CuS nanosheets, S atoms are exposed on the ridges and Cu atoms are embedded in the grooves (Figure b). The exposed S atoms have much weaker hydrogen bonding with H 2 O molecules, compared with that between O atoms and H 2 O molecules. As a result, the PAN@CuS fabric shows a lower water-evaporation enthalpy (Figure b). In addition, the sunflower-inspired hierarchical PAN@CuS fabric is further equipped in a heliotropic evaporation model.…”
mentioning
confidence: 99%
“…2(b). It is interesting to note that the thiocyanate anion in {Me 3 N(CH 2 ) 2 NMe 3 }(SCN) 2 behaves the same way by showing close contacts between the nitrogen atom of the thiocyanate and the methyl hydrogens on one hand, and also between the sulfur atom and methylene hydrogens on the other hand [18].…”
Section: Resultsmentioning
confidence: 95%
“…Structural information on hexaalkyl-1,2-ethylenediammonium salts containing simple anions such as halides or pseudohalides is rather sparse comprising {Me 2 BuN(CH 2 ) 2 NMe 2 Bu}Br 2 · 2H 2 O [14], {Me 3 N(CH 2 ) 2 NMe 3 }I 2 [15], {Me 2 [Et(CH 2 ) n ]-N(CH 2 ) 2 NMe 2 [(CH 2 ) n Et]}X 2 (X = Br, n = 10 [16]; X = I, n = 10, 14 [17]), and {Me 3 N(CH 2 ) 2 NMe 3 }-(SCN) 2 [18]. In some of these crystals, hydrogen bonding networks lead to the formation of extended supramolecular structures.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the generic weakness of CH as a proton donor, computations have shown that it is strong enough to engage F as an acceptor [79,103,[124][125][126][127][128][129][130][131]. Other proton-accepting atoms are S [100, [132][133][134][135][136], even as strong as 7 kcal/mol [137,138], Cl [139][140][141][142] or I [143]. Even an atom as weakly basic as P [144,145] can serve this function as can carbenes [146].…”
Section: Recent Workmentioning
confidence: 99%